New Candidates for Organic-rich Regions on Ceres - J. L. Rizos; J. M. Sunshine; R. T. Daly; A. Nathues; C. De Sanctis; A. Raponi; J. H. Pasckert; T. L. Farnham; J. Kloos; J. L. Ortiz (The Planetary Science Journal)
We explore the spatial distribution of organics on Ceres using the visible and near-infrared data collected by the Dawn mission. We employ a spectral mixture analysis (SMA) approach to map organic materials within the Ernutet crater at the highest available spatial resolution, thereby revealing a discontinuous, granular distribution and a possible association with an ancient crater on which Ernutet has been superimposed. The SMA technique also helps us identify 11 new areas as potential sites for organics. These regions are predominantly located within craters or along their walls, resembling the distribution pattern observed in Ernutet, which implies a possible geological link with materials exposed from beneath the surface. In one of these candidate regions situated in the Yalode quadrangle, we detected the characteristic 3.4 μ m absorption band in the infrared spectrum, indicative of organics and carbonates. By combining the spatial resolution of the Framing Camera data with the spectral resolution of the Visual and Infrared Imaging Spectrometer using SMA, we investigated the distribution of the 3.4 μ m band in this quadrangle. The absorption pattern correlates with the Yalode/Urvara smooth material unit, which formed after significant impacts on Ceres. The association of organic-rich materials with complex and multiple large-impact events supports an endogenous origin for the organics on Ceres.